Outcomes of births attended by private midwives in the Gauteng Province of South Africa: A retrospective cohort study - Christél Jordaan-Schlebusch; Catharina Susanna Minnie (Elsevier, 2023)
Midwives are important role players in providing women-centred care for low-risk pregnant women.South African women use either public or private health care services during pregnancy and birth. As the public sector is overburdened, women do not receive a high level of continuity of care there. The private sector is mainly obstetrician-led and intervention-driven. Private midwife-led care is available in South Africa, but is limited to the major cities. No evidence could be found about the outcomes of private midwife-led care in South Africa.The objective reported in this paper was to compare the outcomes of and interventions during births attended by private midwives in Gauteng with the latest Cochrane review on midwife-led care.A retrospective cohort design was used to audit the birth registers of private midwives in Gauteng, focusing on outcomes and interventions as in the most recent Cochrane review on midwife-led care.The maternal and neonatal outcomes of Gauteng midwives' patients were reassuring. Compared to women in the Cochrane review, significantly more Gauteng women had an intact perineum (53.4% vs 29%), fewer had interventions such as induction of labour (9.6% vs 19.3%), but more had caesarean sections (19.3% vs 13.3%). Overall foetal loss (0.3% vs 2.7%) and NICU admissions (4.3% vs 7.1%) occurred significantly less frequently in the Gauteng sample.The study's findings indicated that private midwife-led care in Gauteng compared well with that in the rest of the world in terms of outcomes and intervention rates.